SpectralTDF: transition densities of diffusion processes with time-varying selection parameters, mutation rates and effective population sizes - Steinrücken, Matthias (Bioinformatics, 2016)
Motivation: In the Wright–Fisher diffusion, the transition density function describes the time evolution of the population-wide frequency of an allele. This function has several practical applications in population genetics and computing it for biologically realistic scenarios with selection and demography is an important problem. Results: We develop an efficient method for finding a spectral representation of the transition density function for a general model where the effective population size, selection coefficients and mutation parameters vary over time in a piecewise constant manner. Availability and implementation: The method, called SpectralTDF, is available at https://sourceforge.net/projects/spectraltdf/. Contact: yss@berkeley.edu Supplementary information: Supplementary data are available at Bioinformatics online.